1981
DOI: 10.1111/j.1600-051x.1981.tb02027.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative antibody titers to Actinobacillus actinomycetemcomitans in juvenile periodontitis, chronic periodontitis and periodontally healthy subjects

Abstract: Circulating antibody levels to four strains of Actinobacillus actinomycetemcomitans (Aa) were determined by means of an indirect immunofluorescent technique in three groups of 21 subjects each, including one with juvenile periodontitis (JP), one with chronic periodontitis (CP) and one free of periodontal disease (N). Mean levels of antibody to Aa were significantly elevated in the JP group as compared to the CP and N groups with respect to strains Y4, 29522 and 29524, but not strain 29523. Since strains Y4, 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
0
2

Year Published

1983
1983
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(66 citation statements)
references
References 22 publications
5
59
0
2
Order By: Relevance
“…Antigenic studies have described three primary serotypes of A. actinomycetemcomitans (Zambon et al, 1983b;McArthur et al, 1986;Ebersole et al, 1994b), although additional serotypes have been identified in some humans (Zambon et al, 1983a;McArthur et al, 1986;Chung et al, 1989;Ohgi and Kamoi, 1990;Asikainen et al 1991Asikainen et al , 1992Ebersole et al, 1991). Our patient population showed elevated antibody specific for A. actinomycetemcomitans serotype b (Ebersole and Holt, 1991) and supported the presence of serotype b as the primary type in human periodontitis patients (Listgarten et al, 1981;Gmiur et al, 1986;Genco et al, 1988;Gunsolley et al, 1988;Califano et al, 1989;Ebersole, 1990). Serum IgG antibody responses to outer membrane proteins and sonicate antigens from A. actinomycetemcomitans serotype c have been described (Watanabe et al 1989).…”
Section: Introductionsupporting
confidence: 76%
“…Antigenic studies have described three primary serotypes of A. actinomycetemcomitans (Zambon et al, 1983b;McArthur et al, 1986;Ebersole et al, 1994b), although additional serotypes have been identified in some humans (Zambon et al, 1983a;McArthur et al, 1986;Chung et al, 1989;Ohgi and Kamoi, 1990;Asikainen et al 1991Asikainen et al , 1992Ebersole et al, 1991). Our patient population showed elevated antibody specific for A. actinomycetemcomitans serotype b (Ebersole and Holt, 1991) and supported the presence of serotype b as the primary type in human periodontitis patients (Listgarten et al, 1981;Gmiur et al, 1986;Genco et al, 1988;Gunsolley et al, 1988;Califano et al, 1989;Ebersole, 1990). Serum IgG antibody responses to outer membrane proteins and sonicate antigens from A. actinomycetemcomitans serotype c have been described (Watanabe et al 1989).…”
Section: Introductionsupporting
confidence: 76%
“…The elevated antibody against A. actinomycetemcomitans serotype b (Y4) in localized AgP is in accordance with earlier studies (10, 22, 27). Ranney et al.…”
Section: Discussionsupporting
confidence: 92%
“…According to this notion, high levels of systemic antibodies are thought to “contain” the extent of periodontal tissue support loss, while poor ab responses are expected to contribute to a more widespread periodontal destruction. This perception has been primarily founded on data from several studies in the early 80s that investigated serum ab responses to A. actinomycetemcomitans (Listgarten et al 1981, Ebersole et al 1982, Ranney et al 1982, Genco et al 1985). Using the accepted nomenclature of the time, these studies primarily compared subjects with LJP or GJP and, to a lesser extent, subjects with adult periodontitis, and demonstrated an inverse relationship between titre levels and extent of disease.…”
Section: Discussionmentioning
confidence: 99%